Clinical significance of upper airway dysfunction in motor neurone disease. Issue 9 (September 1994) - García-Pachón, E; Martí, J; Mayos, M; Casan, P; Sanchis, J
Abstract : BACKGROUND–To assess the occurrence, functional characteristics and prognostic value of upper airway dysfunction in motor neurone disease, 27 patients unselected for respiratory symptoms were studied. METHODS–Upper airway function was evaluated by analysis of the maximal flow-volume loop. Neurological diagnosis was established from the clinical history and physical examination. The degree of impairment was quantified by the Appel score. RESULTS–Twelve patients (group A) showed abnormalities of the maximal flow-volume loop consistent with flow limitation (seven patients) or instability of upper airway function (gross oscillations of airflow, five patients). The remaining 15 patients (group B) exhibited a normal or generally reduced maximal flow-volume loop, suggestive of muscle weakness. No differences were observed between groups in general physical condition, rate of disease progression, or duration of disease. CONCLUSIONS–Upper airway dysfunction in patients with motor neurone disease was a frequent finding. It was present more often, but not exclusively, in patients with bulbar features and was unrelated to prognosis.